Identificação, priorização e análise dos fatores críticos para o sucesso na implantação da TPM pelo método AHP - Piechnicki, Ademir Stefano (2013)
The TPM is a Continuous Improvement approach recognized for developing organizational strategies, process optimization and increased competitiveness. However, during its implementation many failures occur and the results do not occur as expected. To reduce these flaws, this study aims to present the Critical Success Factors ( CSFs ) in the implementation of TPM in a group of Brazilian companies winning the award TPM Awards. The FCS were identified through an exploratory research on cases of successful implementations. Once identified, these factors were prioritized by Analytic Hierarchy Process method (AHP), by experts in the TPM methodology. The analyzes clearly demonstrate that the success of TPM methodology depends heavily on the efforts of corporate managers, especially top management . Thus, the key elements that the management should focus on each of the four phases of the program are presented. This process can help managers to give emphasis on the FCS and identify what mistakes should be avoided to increase the chances of success of the TPM program.